The role of the social system in the diffusion of innovation in low to middle income countries: the case of be he@lthy, be mobile. - Ihasz, Orsolya (Cranfield University, 2021)
Actors across the private, public and third sector are increasingly embracing the idea of promoting the use of externally developed social innovations to address important social challenges globally. Successful diffusion of these types of innovations has the potential to offer long term solutions to grand challenges. However, when diffusing innovations into low to middle income countries (LMICs), significant problems arise, particularly due to lack of cross-sectoral alignment in financial and technical resource deployment. This thesis contributes to the understanding of how multiple actors engage in activities to support the diffusion of externally developed social innovations into LMICs. We argue that through purpose-led alignment around a mission-orientated goal that is focused on solving social challenges and through the combining resources and knowledge across all sectors, through the active empowerment of civil society in creating value and continuous feedback loops, externally developed social innovations can contribute greatly to the emergence of new innovation ecosystems in LMICs. A systematic literature review illuminates the role of the social system in successfully enabling widespread diffusion, especially in creating value from the use of the innovation. We propose that the social system perspective, which conceptualise diverse actors engaged in a dynamic process, permits a systems view of diffusion in which long term collaborations and the integration of indigenous knowledge into communication processes are associated with successful diffusion. The role of social systems in value creation is been further investigated through an in-depth case study of the World Health Organization’s Be He@lthy, Be Mobile initiative across three different countries (Senegal, Sudan and India). The case highlights how civil society drives the diffusion process through its ability to manoeuvre across the social system and to actively search for innovative solutions. While our research has implications for the introduction of improved strategic investment across sectors it also contributes to the theory of innovation diffusion by moving away from an innovation- centric view and instead adopting a systems-centric view. It hence allows us both to view diffusion as a co-creation process and to reconfigure adopter and diffuser communities into one conceptual field.
Keywords: Innovation diffusion; social innovation; social system; value creation; systematic literature review; enabling technology; low to middle income country